FACTORS THAT INFLUENCE COMPANY VALUE WITH CAPITAL STRUCTURE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) - Novianti, Tina (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to examine the factors that influence the value of a company. Investment Decisions, Company Size, Liquidity, Profitability, Institutional Ownership and Dividend Policy have a partial and simultaneous effect on Company Values ​​in manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach, namely by testing the associative relationships of measured research variables (parametric). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the research period of 2013 to 2017. The population in this study are 26 companies and to determine the size of the sample using a sample method that is saturated sampling or census. The results of the study are simultaneously from the 6 independent variables on the dependent variable Y (Company Value) of 0.70 x 100% = 70%. In other words, 70%. Company values ​​can be explained by the 6 independent variables (TAG, Ln-TA, CR, ROE, INST, DPR), partially the size of the company has a negative and not significant effect on firm value. Capital structure is proven as a moderating variable that influences the relationship of independent variables with dependent variables.